Ultrasonic cleaning of plant roots in their preparation for analysis on heavy metals = Zastosowanie metody oczyszczania ultradźwiękami w analizie koncentracji metali ciężkich w materiale korzeniowem pobranym z doświadczenia wazonowego - Cuske, Mateusz; Karczewska, Anna; Gałka, Bernard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper focuses on ultrasonic method used for cleaning of root material collected from a pot experiment. In the experiment, red fescue was grown on differently contaminated soils amended with organic additions. Determined were total concentrations of Cu and Zn in root material prepared for analysis by hand washing and the use of ultrasonic bath. The results indicate significant differences between the two methods.
Keywords: ultrasonic; contaminated soils; heavy metals; pot experiment; roots; ultradźwięki; gleby zanieczyszczone; metale ciężkie; doświadczenie wazonowe; korzenie